Resident evil : Apocalypse [videorecording (DVD)] - Jovovich, Milla; Guillory, Sienna, 1975-; Fehr, Oded, 1970- (Columbia TriStar Home Entertainment, 2004)
After the re-opening of the Hive and the T-Virus, the Umbrella Corporation quarantines the whole city, disabling anyone at all from leaving. Among those trapped within, are members of the suspended STARS group. To survive the mess around them, Alice, now a genetically modified project, has to accept a deal with Dr. Ashford, a scientist whose daughter has gone missing, and escort her out of the city. If Alice accepts, he'll ensure that the group are safely flown out of the quarantined city before the deadly Nemesis eliminates them all.